A Review and Analysis of Nuclear Hydrogen Production in Generation IV Reactors - Arijit Saha Ayon; Ashiqur Rahman Alif; A. S. M. Nasim (International Journal of Nuclear Security, 2024)
Hydrogen is becoming increasingly vital as a chemical element in the progress of human civilization. Hydrogen finds application in the creation of ammonia, the manufacturing of nitrogen-based fertilizers, and a wide range of organic compounds, including methanol and propulsion fuel for space exploration missions. Additionally, there are ongoing experiments in the automotive industry to harness hydrogen-based fuel cells as an alternative power source. In modern technology, multiple methods and strategies for hydrogen production originate from diverse sources, such as fossil fuels, renewable energy, nuclear energy, and more. Generation IV nuclear reactors significantly affect the production of hydrogen. These reactors operate at elevated temperatures, and at these temperatures, heat transfer processes are more efficient for producing significant quantities of hydrogen. Within the realm of hydrogen production, both thermochemical and electrolysis (hybrid) techniques offer promising potential, particularly when integrated with Generation IV nuclear power reactors. This study undertakes a comparative analysis of various nuclear Generation IV reactor types concerning their capacity for substantial hydrogen production techniques while also exploring potential adaptations.
Keywords: Hydrogen; Generation IV Reactor; Electrolysis; Sulphur-Iodine; Steam Reforming; GFR; VHTR